Sociālā uzņēmējdarbība; potenciāli un izaicinājumi - Khadraoui, Houdhifa (Latvijas Universitāte, 2018)
Jaunā nozare - sociālā uzņēmējdarbība – saņem aizvien vairāk uzmanības un popularitātes gadu laikā, un tomēr pastāv liela plaisa starp tās popularitāti un empīriskajiem pētījumiem, kuri rakstīti, lai izpētītu izaicinājumus, ar kuriem saskaras sociālie uzņēmēji. Lielākā daļa pētījumu ir veikti fokusējoties uz bezpeļņas organizācijām, turpretī organizācijas, kuras darbojas ar peļņu, ir saņēmušas daudzreiz mazāk uzmanības. Sociālā uzņēmējdarbība ir sarežģīts, daudzveidīgs fenomens, kurš ietver dažādus organizatoriskos veidus un aktivitātes, neskatoties uz to sociālās uzņēmējdarbības popularitāte tiek pārspēkota ar dažādajiem pieņēmumiem, ņemot vērā, ka dažādām sabiedrības grupām sociālā uzņēmējdarbība nozīmē dažādas lietas. Šī darba mērķis ir izpētīt problēmas, kas skar sociālos uzņēmumus, un izcelt tā\o potenciālu, kā arī precizēt nepareizus pieņēmums par šo tēmu. Darba izveidē tika izmantota kvalitatīvā datu apstrāde – intervijas ar sociālo uzņēmumu vadītājiem ar dažādu pieredzi no dažādām valstīm un reģioniem.Rezultāti rāda, ka sociālie uzņēmumi ir līdzīgi vispārpieņemtajiem uzņēmumiem, dalot ar tiem dažādas kopīgas pazīmes, problēmas. Kā arī sociālajiem uzņēmumiem ir unikāla loma ne tikai radīt ekonomisko izaugsmi, bet arī veicināt labklājību, atrodot risinājumus sociālām problēmām. Lai gan šī loma ir ļoti svarīga, sociālie uzņēmumi nav pārāk atzīti un tie vēl joprojām saskaras ar dažādām problēmām.

The nascent field of social entrepreneurship has received growing attention, and popularity over the years, yet there is a huge gap between its popularity and the empirical research are made to investigate the challenges that are faced by social entrepreneurs, as majority of the researches done are mainly focused on non-profit organizations, however the for-profit context of it received less attention. Social entrepreneurship is a diverse, complex phenomenon that includes different organizational forms and activities, and occupies huge part of the world economy, emerging as a major economic force throughout the world. The pressing social needs nowadays require new approach beside the reliance on the market and the state who are slacking behind, making room for the emerging third sector “social entrepreneurship”, however, that does not mean that the third sector is the one that going to save the day. It only prove the necessity of this sector to responds to the public needs, in fact all the three sector should be mobilized together in order to make the needed progress. Nevertheless the popularity of social entrepreneurship it is still challenged by different definitions, where it means different things to different people, the aim of this thesis is to investigate the challenges that are facing social enterprises, and highlight its potentials, moreover to clear the misconceptions surrounding the concept, by adapting qualitative method approach, gathering data from interviews with different managers of social enterprises, from different backgrounds, regions, and countries. The results of this research shows that social enterprises are similar to business enterprises sharing universal characteristics with them, as well as challenges, moreover, social enterprises have a unique role to not only create economic growth but to uplift the society, by finding solutions for pressing social needs, even though this role is very important, social enterprises are not well acknowledged, and still face unique challenges.
Social Entrepreneurship; potentials and challenges
Keywords: Vadībzinātne; Social entrepreneurship; entrepreneurs; innovation; social enterprises; non-profit organization